Common polymorphic transcript variation in human disease - Fraser, Hunter B.; Xie, Xiaohui (Genome Research, 2009)
Most human genes are thought to express different transcript isoforms in different cell types; however, the full extent and functional consequences of polymorphic transcript variation (PTV), which differ between individuals within the same cell type, are unknown. Here we show that PTV is widespread in B-cells from two human populations. Tens of thousands of exons were found to be polymorphically expressed in a heritable fashion, and over 1000 of these showed strong correlations with single nucleotide polymorphism (SNP) genotypes in cis. The SNPs associated with PTV display signs of having been subject to recent positive selection in humans, and they are also highly enriched for SNPs implicated by recent genome-wide association studies of four autoimmune diseases. From this disease-association overlap, we infer that PTV is the likely mechanism by which eight common polymorphisms contribute to disease risk. A catalog of PTV will be a valuable resource for interpreting results from future disease-association studies and understanding the spectrum of phenotypic differences among humans.